Optimalisasi Monitoring Traffic Komunikasi Data dan Penggunaan Resource Network Equipment Dalam Jaringan Lokal di IBI-K 1957 - Syamsu Hidayat; Joko Susilo (NUANSA INFORMATIKA, 2024)
Monitoring a network and its device resources is very necessary in a data communications network, because based on the monitoring results, we can find out how much network resources are used, especially firewall and server devices. The monitoring carried out previously used an application that was accessed via remote desktop, where the application could only monitor data communication traffic used by users on the network. The use of remote desktops is very vulnerable from a network security perspective because it is often the target of exploration by cybercriminals or so-called black hackers. For this reason, monitoring of network devices is optimized using an open-source based application that can visualize the results of monitoring these devices on a web basis. By implementing this application, it can be concluded that it is able to fulfill the need for monitoring the use of resources and data communication traffic in the network so that if there is something unusual it can be immediately addressed by a System Administrator.